1987
DOI: 10.1002/j.1537-2197.1987.tb08778.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Impact on Sexual vs. Asexual Reproductive Success in Arisaema Triphyllum

Abstract: Populations of Arisaema triphyllum commonly harbor a systemic fungal pathogen, Uromyces ari‐triphylli, which reduces leaf area and leaf longevity. Infected plants produced 42% fewer asexual progeny (cormlets). Furthermore, all asexual progeny from infected parents were themselves infected with Uromyces. Mean seed production of infected plants was only 21% of that among healthy plants. A hand pollination experiment demonstrated that 1) infected male plants can produce viable pollen, 2) the low seed production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Changes in the abundance of plant enemies (e.g., herbivores, pathogens, nectar robbers), plant mutualists (e.g., mycorrhizal fungi), and pollinator enemies (predators) may all affect interactions between plants and pollinators and thus the magnitude of pollen limitation (Table 1). Whereas many studies have factorially manipulated plant enemies and pollen receipt (Bertness & Shumway 1992, Garcia & Ehrlen 2002, Holland 2002, Juenger & Bergelson 1997, Krupnick & Weis 1999, Lehtila & Syrjanen 1995, Mizui & Kikuzawa 1991, Mothershead & Marquis 2000, only Parker (1987) found a significant interaction; enemies decreased the magnitude of pollen limitation. Other interacting species in the community have received much less attention and should be the target of future empirical work.…”
Section: Other Interacting Speciesmentioning
confidence: 99%
“…Changes in the abundance of plant enemies (e.g., herbivores, pathogens, nectar robbers), plant mutualists (e.g., mycorrhizal fungi), and pollinator enemies (predators) may all affect interactions between plants and pollinators and thus the magnitude of pollen limitation (Table 1). Whereas many studies have factorially manipulated plant enemies and pollen receipt (Bertness & Shumway 1992, Garcia & Ehrlen 2002, Holland 2002, Juenger & Bergelson 1997, Krupnick & Weis 1999, Lehtila & Syrjanen 1995, Mizui & Kikuzawa 1991, Mothershead & Marquis 2000, only Parker (1987) found a significant interaction; enemies decreased the magnitude of pollen limitation. Other interacting species in the community have received much less attention and should be the target of future empirical work.…”
Section: Other Interacting Speciesmentioning
confidence: 99%
“…Alternatively, enemies may reduce plant resources, such that reproduction is resource limited rather than pollen limited. For example, Parker (1987) demonstrated that healthy Arisaema triphyllum plants were strongly pollen limited whereas those infected with Uromyces were not, most likely because the infected plants did not have the resources to allocate to maturing more seeds. Future empirical studies should expand this work to understand the evolutionary consequences for mating system of these enemy‐induced changes in pollen limitation and mate availability.…”
Section: Maintenance Of Mixed Mating By Enemies Via Effects On Model mentioning
confidence: 99%
“…Sexually transmitted diseases are ubiquitous among animals (Morand 1993;Morand and Faliex 1994;Lockhart et al 1996;Knell and Webberley 2004). In plants, enemies transmitted among flowers by pollinating agents (e.g., bees, wind) are considered sexually transmitted (Parker 1992;Kaltz and Schmid 1995;Antonovics 2005). Wolf et al (unpubl.…”
Section: Sexually Transmitted Enemies Reduce Inbreeding Depressionmentioning
confidence: 99%
“…Fungal pathogens that severely affect plant reproduction have been suggested to be a potentially important factor in the evolution of a host's reproductive system (Levin 1978, Clay 1991, Antonovics 1992. A few studies have shown differences between diseased and healthy plants in the amount of selfed vs. outcrossed seed or asexual vs. sexual progeny produced (Clay 1984, Parker 1987. Pathogens would also influence the breeding system of healthy plants (1) if differences in infection rates existed between sexual morphs or male and female phases, (2) if differences DEBORAH L. MARR in fitness costs existed between female and male function (e.g., pollen dispersal is affected more than seed production), or (3) if pollen limitation is greater in populations with diseased individuals.…”
Section: Introductionmentioning
confidence: 99%